1989
DOI: 10.1159/000153859
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens, Blood Groups and Serum Protein Groups in Patients with Intermittent Claudication

Abstract: HLA (A and B) antigens, blood group systems (ABO, Rh, MNSs, P, Kell, Lewis and Duffy) and serum group systems (Hp, Tf, Pi, C3 and C4) were studied in patients with intermittent claudication (IC) and controls. HLA antigen A 28 was significantly more common, and blood group 0 was significantly less common among the patients than among the controls. A comparison between patients with IC and those with abdominal aortic aneurysms showed a significant difference between these two groups concerning the MN blood group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For PVD, we observed a pooled OR of 1.45 (95% CI 1.35–1.56) for non‐O relative to O. Interestingly, whilst only some used objective diagnosis [35,36,39,40], or comparable controls [21,35,38], the findings were highly consistent. For CIAO, pooling of the small number of available studies revealed that blood group non‐O produces a small, but significant, increased risk of CIAO (OR 1.14, 95% CI 1.01–1.27).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…For PVD, we observed a pooled OR of 1.45 (95% CI 1.35–1.56) for non‐O relative to O. Interestingly, whilst only some used objective diagnosis [35,36,39,40], or comparable controls [21,35,38], the findings were highly consistent. For CIAO, pooling of the small number of available studies revealed that blood group non‐O produces a small, but significant, increased risk of CIAO (OR 1.14, 95% CI 1.01–1.27).…”
Section: Discussionmentioning
confidence: 68%
“…The key limitations to MI/angina studies were not reporting result uncertainty (12 studies) [17–28] and a lack of control for potential population stratification (12 studies) [17,22–24,26–33]. For PVD, no study reported result uncertainty and/or provided detailed demographic data [21,34–40]. Studies on CIAO were generally of good quality, although four did not define CIAO using modern imaging [21,41–43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation